Asset Size and Profitability of Life Insurance Companies in Nigeria. A Panel Data Approach - Aduloju, Sunday Adekunle; Akindipe, Oluwaleke Ebenezer (Acta Universitatis Danubius. Œconomica, 2022)
The magnitude of a company is a crucial element in evaluating organizational ascendancy while economies of scale are an advantage for most large corporations. This study examined how the size of life insurance companies' asset base affect profitability in Nigeria between 2011 and 2021. Data on assets of life insurance companies and the insurance digest of the Nigerian Insurers Association (NIA) were used to determine profit after tax and asset size for the relevant period. The data's stationarity test revealed that the data are stationary at the significance levels of 1%, 5%, and 10%. Data are statistically significant because the calculated probability (F-statistic) value from the ordinary least squares regression is smaller than the 0.05 significant value. The profit after tax is accounted for by 73.8811 percent of the total assets of life insurance firms, according to the computed linear coefficient of determination (R2= 0.738811). The study's findings report that asset size affects the financial success of insurance businesses in Nigeria.